A Prospective Study of Religiousness and Psychological Distress Among Female Survivors of Hurricanes Katrina and Rita - Chan, Christian S. (2012)
This prospective study examined the pathways by which religious involvement affected the post-disaster psychological functioning of women who survived Hurricanes Katrina and Rita. The participants were 386 low-income, predominantly Black, single mothers. The women were enrolled in the study before the hurricane, providing a rare opportunity to document changes in mental health from before to after the storm, and to assess the protective role of religious involvement over time. Results of structural equation modeling indicated that, controlling for level of exposure to the hurricanes, pre-disaster physical health, age, and number of children, pre-disaster religiousness predicted higher levels of post-disaster (1) social resources and (2) optimism and sense of purpose. The latter, but not the former, was associated with better post-disaster psychological outcome. Mediation analysis confirmed the mediating role of optimism and sense of purpose.